Unraveling the effect of chloride ion on the corrosion product film of Cr-Ni- containing steel in tropical marine atmospheric environment. (December 2022) - Dong, Baojun; Liu, Wei; Chen, Longjun; Zhang, Tianyi; Fan, Yueming; Zhao, Yonggang; Li, Hai; Yang, Weijian; Sun, Yipu
Abstract: The effect of Cl - concentration on the corrosion behavior of Cr-containing steel in tropical marine atmospheric environment is systematically studied. Cl - ions affect the adsorption amount of water film and then affected O2 diffusion. They reduce the generation of NiFeO4 and Cr(OH)3 and destroy the electronegativity of inner film, further weakening the homologous enrichment of Ni, Mo and Cr and intensifying the penetration of Cl - ions. The amount of NiO and Cr2 O3 decreases due to oxygen reduction, which reducrs FeOOH nucleation sites and promotes the large-size FeOOH generation, leading to increase the pores in the corrosion product films. Highlights: Adding a small amount of Cr to Ni-steel reduces its corrosion rate. Cr element promote more NiFe2 O4 forming and attract more Ni 2+ and Cr 3+ ions, repelling and shielding negatively charged Cl - . High Cl - concentration reduces the content of O2, inhibiting the formation of NiFe2 O4 and Cr(OH)3 .